The Impact of Generative Content on Individuals Privacy and Ethical Concerns - Sudhir Bale, Ajay; Dhumale, R. B.; Beri, Nimisha; Lourens, Melanie; Varma, Raj A.; Kumar, Vinod; Sanamdikar, Sanjay; Savadatti, Mamta B. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The rise of AI and ML-fueled generative content technologies has altered every stage of the content life cycle, from creation to distribution to consumption. There are many positive outcomes from these breakthroughs, but there are also serious ethical and privacy problems. The purpose of this work is to investigate the wide-ranging effects of generative content on personal data security and ethical considerations. The article dives into the privacy concerns that may arise from using generative material. Since this kind of technology depends heavily on user data, the ease with which accurate and tailored content may be generated raises concerns about data privacy. Unauthorized content synthesis, which may lead to the proliferation of bogus data, counterfeits, and other types of illicit tampering, is also a source of worry. We have attempted to consider all these implications and delve into them to bring out possible solutions. We are optimistic that this article will provide future insights into the research of generative content and its ethical considerations.